Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ana.24943
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of coma recovery after cardiac arrest with blinded pupillometry

Abstract: Reduced quantitative PLR correlates with postanoxic brain injury and, when compared to standard multimodal assessment, is highly accurate in predicting long-term prognosis after CA. This is the first prognostication study to show the value of automated pupillometry using a blinded approach to minimize self-fulfilling prophecy. Ann Neurol 2017;81:804-810.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 30 publications
1
60
0
1
Order By: Relevance
“…Preliminary single-center studies, evaluating the value of quantitative pupillometry, focused exclusively on the qPLR and found variable cut-offs of 100% specificity for poor prognosis, with thresholds varying from 10% [16] to 13% [17, 18]. These studies used other devices that did not compute automated NPi.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary single-center studies, evaluating the value of quantitative pupillometry, focused exclusively on the qPLR and found variable cut-offs of 100% specificity for poor prognosis, with thresholds varying from 10% [16] to 13% [17, 18]. These studies used other devices that did not compute automated NPi.…”
Section: Discussionmentioning
confidence: 99%
“…1. In the subset of patients in whom pupillometry measurements were performed at days 6 and 7 (n = 30), q-PLR remained significantly lower in patients with delirium (median 22 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 30 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] in non-delirious patients at day 6, and 27 [25][26][27][28][29][30][31] vs. 35 [27][28][29][30][31][32][33][34][35][36][37][38] at day 7; both p < 0.05).…”
Section: Associations Between Icu Delirium and Quantitative Pupillarymentioning
confidence: 99%
“…In the last several years, quantitative assessment of pupillary light reflex (PLR) has emerged as a promising modality for predicting neurological outcomes in post-CA patients. Several publications reported the prognostic superiority of the quantitative assessment of PLR over the qualitative evaluation of PLR before 72 h after CA [5][6][7][8][9]. Recently, we have reported that quantitative values of PLR in survivors or in patients with favorable neurological outcomes were consistently greater than values in non-survivors or in patients with unfavorable outcomes, respectively, within 72 h following the return of spontaneous circulation (ROSC) after OHCA [9].…”
Section: Introductionmentioning
confidence: 99%